Midsagittal and bilateral facial soft tissue thickness: A cone-beam computed tomography assessment of Brazilian living adults - Barros, F. [UNESP] (2021)
Forensic Facial Reconstruction (FFR) is a technique that enables the recognition of an individual, by modeling the contours of facial tissues on a skull found without identification. It it is necessary to know the facial soft tissue thickness (FSTTs) that covers some craniometric points in the underlying skull to perform a FFR, as they are used as a basis for obtaining the facial contour. The objective of this study was to measure FSTTs of living adult Brazilian subjects, using images from cone beam computed tomography (CBCT), considering the variables sex, ancestry, age and body mass index. Twenty-one anatomical landmarks (10 midsagittal and 11 bilateral) were measured, using Osirix Lite software. A total of 106 images were analyzed (71 females and 35 males). It was observed that, in general: 1. males presented thicker facial soft tissues than females; 2. older individuals had higher FSTT values than younger ones; 3. black individuals presented higher means, compared with white individuals, and; 4. subjects with BMI above normal had thicker facial tissues than those with normal BMI. However, more studies with the Brazilian population are necessary. In order to obtain data related to subgroups concerning, for example, sex and ancestry, sex and age, or sex and BMI, larger samples must be considered.